Dielectric-based tissue thickness measured during radiofrequency ablation catheter. (19th May 2022) - Schillaci, V; Stabile, G; Arestia, A; Shopova, G; Agresta, A; Salito, A; De Simone, A; Solimene, F
Abstract: Funding Acknowledgements: Type of funding sources: None. A new dielectric-based method of KODEX-EPD mapping system (EPD Solutions) for measuring tissue thickness at the catheter-tissue interface has recently been developed. We reported preliminary data on real-time catheter-based measuring myocardial wall thickness in vivo, during typical atrial flutter (AFL) RF ablation. The Kodex version used to perform this type of analysis is a version not commercially available yet but only for case replay and research purpose, not used in clinical practice. The study population consisted of 12 consecutive patients, suffering from symptomatic paroxysmal or persistent cavo-tricuspid isthmus (CTI) dependent. The Wall Viewer (WV) function is measured by assessing a series of dielectric signals derived directly from real-time local interrogation of the catheter-tissue interface. WV is displayed in millimeters, with either high or low confidence levels per met or unmet prerequisite acquisition criteria respectively and it is displayed as a color code scale (Fig. 1, A). The anatomy of the CTI was identified using the 4mm MAP-iT irrigated ablation catheter. A suitable starting point for the ablation, in the proximity of the tricuspid valve, and a final location in the junction between the inferior vena cava and the right atrium, were precisely defined based on electrograms recorded. Subsequently, "point by point" CTI ablation was performed delivering RF energy with 30/40 Watts for 20-40 seconds with an interlesion distance ≤6 mm. 9 patients had paroxysmal common AFL, 3 persistent common AFL. The mean age was 64±9 years, 10 (83%) were male. The mean body mass index was 30±6, 9 (75%) patients had hypertension, and 1 (8%) had coronary artery disease. The mean procedure time was 37±13 min, the mean fluoroscopic time was 690±378 s, the mean RF time 763±205 s, with a mean number of RF pulses of 28±7. The mean cavo-tricuspid isthmus length was 29.5±2.6 mm. The atrial wall thickness was significantly higher close to the tricuspid annulus than close to the inferior vena cava (3.6±0.5 mm vs 2.4±0.3 mm, p<0.001) and a trend towards a progressive decrease of atrial wall thickness was observed moving the mapping catheter from the tricuspid valve to the inferior vena cava (Fig. 1, B). Acute bidirectional cavo-tricuspid isthmus block was achieved in all patients without any complications. We first describe a new mapping technology that allows atrial wall thickness measurement and, as expected, the wall thickness was higher close the tricuspid annulus and lower towards the inferior vena cava. The possibility to calculate the substrate thickness before RF delivery could deeply change the way to perform RF ablation, allowing a tailored energy delivery thus increasing the efficiency of the procedures and potentially reduction of the risk of complications.